THE ROLE OF DIGITAL TECHNOLOGIES IN ENHANCING THE EFFICIENCY OF MECHANISMS FOR IMPLEMENTING PUBLIC POLICY ON MANAGING SOCIAL CONFLICTS IN UKRAINE - STADNIICHUK, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the article, the role of digital technologies in enhancing the efficiency of mechanisms implementing public policy for managing social conflicts in Ukraine is examined. The analysis underscores the importance of utilizing digital innovations, such as e-governance, mobile applications, and digital platforms, in fostering interaction between civil society and the government. The advantages of digital tools, including increased transparency, active citizen participation, and prompt response to social conflicts, are highlighted. Emphasis is placed on how the development of digital literacy in the population contributes to the implementation of innovations and the establishment of a sustainable mechanism for managing social conflicts in Ukraine.It is emphasized that Ukraine, with its multi-layered socio-cultural environment, faces unique challenges in the realm of social conflicts. Digital technologies, considering the peculiarities of the national context, can act as a catalyst for improving understanding among various social groups, providing broader access to information, and enabling the expression of diverse perspectives.In the conclusions of the article, the potential of digital technologies as tools for constructively resolving social conflicts and strengthening social coordination is highlighted. The importance of continued investments in digital infrastructure and programs for the development of digital literacy is underscored for the sustainable implementation of digital mechanisms for managing social conflicts in Ukrainian society.
Keywords: public administration; digital technologies; social conflicts; business; efficiency